Microorganisms’ Footprint in Neurodegenerative Diseases - Dehhaghi, Mona; Kazemi Shariat Panahi, Hamed; Guillemin, Gilles J. (Frontiers in Cellular Neuroscience, 2018)
Advancement of science has gifted the human a longer life; however, as neuron cells do not regenerate, the number of people with neurodegenerative disorders rises with population aging. Neurodegenerative diseases occur as a result of neuronal cells loss caused by environmental factors, genetic mutations, proteopathies, and other cellular dysfunctions. The negative direct or indirect contributions of various microorganisms in onset or severity of some neurodegenerative disorders and interaction between human immune system and pathogenic microorganisms has been portrayed in this review. This association may explain the early onset of neurodegenerative disorders in some individuals, which can be traced through detailed study of health background of these individuals for infection with any microbial disease with neuropathogenic microorganisms (bacteria, fungi, viruses). A better understanding and recognition of the relation between microorganisms and neurodegenerative disorders may help researchers in development of novel remedies to avoid, postpone, or make neurodegenerative disorders less severe.